On the Geometry of Curvature Radiation and Implications for Subpulse Drifting - McSweeney, S.; Bhat, Ramesh; Tremblay, S.; Deshpande, A.; Wright, G. (Institute of Physics Publishing, 2019)
The phenomenon of subpulse drifting offers unique insights into the emission geometry of pulsars, and is commonly interpreted in terms of a rotating carousel of "spark" events near the stellar surface. We develop a detailed geometric model for the emission columns above a carousel of sparks that is entirely calculated in the observer's inertial frame, and which is consistent with the well-understood rotational effects of aberration and retardation. We explore the observational consequences of the model, including (1) the appearance of the reconstructed beam pattern via the cartographic transform, and (2) the morphology of drift bands and how they might evolve as a function of frequency. The model, which is implemented in the software package PSRGEOM, is applicable to a wide range of viewing geometries, and we illustrate its implications using PSRs B0809+74 and B2034+19 as examples. Some specific predictions are made with respect to the difference between subpulse evolution and microstructure evolution, which provides a way to further test our model.